The EU’s CBAM in a Turbulent Global Context - A New Horizon for the Green Transition or the Beginning of a New Trade War? - Alfvegren,Gustav (2025)
This thesis investigates the European Union’s Carbon Border Adjustment Mechanism (CBAM) as a novel intersection between climate regulation and international trade law. It explores the extent to which CBAM serves as a legitimate environmental measure under EU and World Trade Organization (WTO) legal frameworks or whether it risks functioning as a de facto instrument of protectionism. This is particularly in the context of rising global trade tensions. The analysis is structured around three core research questions: the legal design and operational structure of the EU CBAM, its compatibility with WTO rules especially to GATT Articles I, III, XX and the geopolitical implications of CBAM within a volatile trade environment shaped by US tariffs and the EU’s green industrial agenda. A doctrinal legal method is combined with a “law in context” approach to situate CBAM within broader economic, geopolitical and legal dynamics. EU legislative acts, including Regulation (EU) 2023/956 and its implementing measures together with the recently proposed ”Omnibus”-package of simplification. The study finds that while CBAM is formally grounded in environmental objectives, its practical application may impose asymmetric burdens on developing countries and risk WTO inconsistency without clear procedural safeguards and transparency. Moreover, CBAM’s role in transatlantic trade relations particularly in light of escalating US tariffs highlights its dual function as both a climate tool and a geopolitical lever. Ultimately, the thesis concludes that CBAM embodies the legal and strategic complexities of advancing sustainable development within an increasingly fragmented global trade order.
Keywords: CBAM; GATT; trade war; non-discrimination; tariff